The obestrung personality: A clinical confounder of obesity - Sanjay Kalra; Komal Verma; Nishant Raizada; Nitin Kapoor (Journal of the Pakistan Medical Association, 2025)
This communication defines and describes the obestrungpersonality trait, which can be a clinical confounder ofobesity. Obestrung (based upon high-strung) personalitycan be defined as a trait characterized by excessivepreoccupation with weight, weight loss, weight lossstrategies and weight loss outcomes. Timelyidentification and alleviation of such attitudes andbehaviour is important. This is because excessive stress,through release of cortisol and proinflammatorycytokines, can hamper efforts at weight loss. Empathiceducation and explanation, along with support from allstakeholders (health care team, family, friends, society) isthe treatment of choice. A few persons may need referralto a mental health professional. Keywords: Barophenotype, bariatric surgery, baromania,obesity, overweight, psychology, psychosomatic disease.